Isolation and Phytochemical Testing of Endophytic Fungi from Imperata cylindrica (L.) Beauv plants. - Makhabbah Jamilatun (International Journal of Basic and Applied Science, 2023)
High drug prices and increasing antibiotic resistance have prompted exploration of natural resources as a source of new antibiotics. The Imperata cylindrica (L.) Beauv. plant is one of the plants used in traditional medicine. Secondary metabolites as bioactive compounds in plants can be obtained through endophytic fungi without having to extract them from plants. Secondary metabolites produced by endophytic fungi can function as raw materials for medicines. This research aims to isolate endophytic fungi and test phytochemicals from Imperata plants to determine the type of secondary metabolites produced. The methods used in this research include isolation and purification of endophytic fungi, identification of endophytic fungi, production of secondary metabolites of endophytic fungi, and screening of phytochemicals resulting from endophytic fungi fermentation. The isolation results showed that there were 7 isolates of endophytic fungi, consisting of 1 isolate from the flower, 3 isolates from the stem, and 3 isolates from the roots. Identification of endophytic fungus using macroscopic and microscopic observations including the genera Fusarium sp., Mucor sp., Penicillium sp., Trichoderma sp., Aspergillus sp., Phytophthora sp. The results of the phytochemical test for endophytic fungi showed that the secondary metabolites produced were flavonoid and saponin compounds. Based on this research, it can be concluded that the endophytic fungi of the Imperata cylindrica (L.) Beauv. plant produces secondary metabolites which have the potential to be developed as medicinal raw material compounds.